Food and beverage marketing in physical external environments of the Universidad Técnica de Ambato - López Flores , Renato Renee (2025)
Food and beverage marketing influences decisions, behaviors and food, turning points of sale into spaces where advertising and various persuasion techniques are displayed and carried out, so that consumers have pleasant shopping experiences. The objective of this study was to analyze the characteristics of the points of sale, the advertising used and the types of products available in the promotion of a healthier and more conscious food environment at the Technical University of Ambato, Ecuador. The method used was quantitative due to its focus on the use of numbers and statistics to collect and analyze data. The results showed policy recommendations based on the Marketing of food and beverages in physical external environments that is configured in decision-making within the institution to promote healthier eating in the university community